Science and technology: Brazilian Agriculture and Embrapa. Pedro Arraes, President of Embrapa. - CGIAR Research Program on Climate Change, Agriculture and Food Security (2012)
Live from Agriculture and Rural Development Day at Rio+20, 18 June 2012 http://www.agricultureday.org Speaker: Pedro Antonio Arraes Pereira, President of the Brazilian Agricultural Research Corporation (Embrapa) Join the discussion: #rio4ag http://www.twitter.com/agricultureday http://www.facebook.com/agricultureday